Genômica comparativa dos roedores Akodontinos Akodon cursor, A. montensis e Necromys lasiurus (Cricetidae: Rodentia) - Naiara Pereira de Araujo (2014)
The Akodontini tribe is characterized by a high level of chromosomal polymorphisms due to Robertsonian rearrangements and pericentric inversions. The karyotypes of Akodon cursor (2n=14, FN=19), A. montensis (2n=24, FN=42) and Necromys lasiurus (2n=34, FN=34) were comparatively analyzed after GTG- and CBG-banding. A great homeology between the chromosomes of the three species was confirmed after GTG banding. CBG-banding revealed few centromeric heterochromatic regions in most chromosomes of the three species. Fluorescent in situ hybridization (FISH) using the (TTAGGG)n sequence as probe showed telomeric signals in the terminal regions of all chromosomes in the three karyotypes. Additionally, interstitial signals that suggest the origin by fusion in pairs 3, 4 and 7 of A. montensis and intensely bright signals associated with the constitutive heterochromatin of chromosomes 3, 15 and X and in the euchromatin of pair 16 of N. lasiurus were observed. Thus, the karyotypes analyzed differed mainly due to Robertsonian rearrangements, pericentric inversions, centromere repositioning and heterochromatin variation. Genomic comparisons using in situ hybridization with total genomic DNAs of each species as probe (GISH) showed conservation of the euchromatic portion of the genomes of the Akodon species and Necromys. Furthermore, a similarity between the repetitive sequences comprising the heterochromatic regions of pairs 1, 3 and 6 and the X chromosome of A. cursor and pair 11 and the X chromosome of A. montensis were observed. These results show an extreme conservation among the genomes of the species analyzed, suggesting that the differences are in the heterochromatic regions. The distribution of the transposable elements LINE-1 (long interspersed repetitive elements), SINE-B1 (short interspersed repetitive elements) and of the endogenous retrovirus mysTR was also checked by FISH in the Akodontini analyzed. The results suggest that these transposable elements may be related to the great chromosomal variation found in the tribe.